The calcium cyanamide and polyethylene blocks the secondary transmission and infection of vegetable leaf diseases - Xie, Xuewen; Chen, Lida; Shi, Yanxia; Chai, Ali; Fan, Tengfei; Li, Lei; Li, Baoju (Frontiers in Plant Science, 2022)
Continuous cropping obstacles, especially soil-borne diseases can cause serious harm to agricultural production and limit the sustainable development of modern agriculture. However, Corynespora blight is an important air-borne disease on cucumber leaves caused by Corynespora cassiicola. The pathogen also could survive in air-dried soil or plant residue for at least one month. However, it is not clear whether soil Corynespora blight residues can infect plants. In this study, we reveal for the first time a new mode of transmission in which leaf blade disease residues in soil can spread again into the air and infect plants. In polyethylene (PE) treatment, cucumber plants grew healthily without disease. However, the content of C. cassiicola in the soil still existed in the PE treatment at 103 spore·g−1. The disease index (DI) of cucumber was less than 3 in calcium cyanamide (CaCN2). After fumigation and film removal and the whole growth period was controlled at a safe level. In addition, the PMA-qPCR detection method of Corynespora blight of cucumber was established for the first time in this study. In summary, CaCN2 and PE treatments are effective ways to block the infection of cucumber leaves by Corynespora blight residues in soil. These treatments are considered to comprise a feasible and sustainable technique for vegetable leaf residues in greenhouses.